Past, present and future challenges in health care priority setting: Findings from an international expert survey. Issue 3 (21st May 2018) - Hall, William; Williams, Iestyn; Smith, Neale; Gold, Marthe; Coast, Joanna; Kapiriri, Lydia; Danis, M.; Mitton, Craig
Abstract : Purpose: Current conditions have intensified the need for health systems to engage in the difficult task of priority setting. As the search for a "magic bullet" is replaced by an appreciation for the interplay between evidence, interests, culture, and outcomes, progress in relation to these dimensions requires assessment of achievements to date and identification of areas where knowledge and practice require attention most urgently. The paper aims to discuss these issues. Design/methodology/approach: An international survey was administered to experts in the area of priority setting. The survey consisted of open-ended questions focusing on notable achievements, policy and practice challenges, and areas for future research in the discipline of priority setting. It was administered online between February and March of 2015. Findings: "Decision-making frameworks" and "Engagement" were the two most frequently mentioned notable achievements. "Priority setting in practice" and "Awareness and education" were the two most frequently mentioned policy and practical challenges. "Priority setting in practice" and "Engagement" were the two most frequently mentioned areas in need of future research. Research limitations/implications: Sampling bias toward more developed countries. Future study could use findings to create a more concise version to distribute more broadly. Practical implications: Globally, these findings could be used as a platform for discussion and decision making related to policy, practice, and research in this area. Originality/value: Whilst this study reaffirmed the continued importance of many longstanding themes in the priority setting literature, it is possible to also discern clear shifts in emphasis as the discipline progresses in response to new challenges.